The Malayan elephant - Mohd. Momin Khan 1935- (Big 5 Malaysian animal series, 2014)
The Malayan Elephant is the largest of the Big Five and conservation challenges require massive funds and great efforts in its management. Malaysia was originally an agro-based economy and for all intents and purposes has been immensely dependent on land. Am extremely serious man-elephant conflict came out. In its search for food the elephant was probably pleasantly surprised to discover that oil plam was edible.